Peptides from chicken processing by-product inhibit DPP-IV and promote cellular glucose uptake: potential ingredients for T2D management. Issue 3 (1st March 2019) - Lima, Rita de Cássia Lemos; Berg, Ragnhild Stenberg; Rønning, Sissel Beate; Afseth, Nils Kristian; Knutsen, Svein Halvor; Staerk, Dan; Wubshet, Sileshi Gizachew
Abstract : A low molecular weight peptide fraction from chicken by-product hydrolysate was found to inhibit DPP-IV in vitro and promote cellular glucose uptake ex vivo . Abstract : Inhibition of dipeptidyl peptidase IV (DPP-IV) and stimulation of muscle glucose uptake are two of the key strategies for management of type-2-diabetes (T2D). In the present study, four protein hydrolysates generated by enzymatic hydrolysis of chicken by-product, i.e., mechanical chicken deboning residue, were evaluated for their DPP-IV inhibitory activity as well as their effect on glucose uptake by skeletal muscle cells. The DPP-IV inhibitory assay was performed at two concentrations (1000 μg mL −1 and 10 μg mL −1 ) for the crude chicken protein hydrolysates. The hydrolysate with the highest DPP-IV inhibition was selected for preparative-scale fractionation using size-exclusion chromatography (SEC). The SEC fractions were tested for DPP-IV inhibitory activity as well as their effect on glucose uptake and metabolic activity of skeletal muscle cells. The muscle cells were treated with the SEC fractions and glucose uptake was measured based on luminescence detection of 2-deoxyglucose-6-phosphate (2DG6P). A fraction with peptides in the lower molecular weight range was shown to promote glucose uptake and to inhibit DPP-IV. Further chromatographic fractionation followed by inhibition assaying of the most potent SEC fraction led to isolation of five refined peptide fractions with more than 80% DPP-IV inhibition, which were subsequently analyzed with LC-HRMS/MS. This led to identification of 14 peptides as potential DPP-IV inhibitors from protein hydrolysates of mechanical chicken deboning residue.